Teaching Staff Competencies from the Perspective of Effective Educational Management - NEGULESCU, Mihail-Cristian; BARBU, Cristina - Mihaela; MIHALCEA, Delia-Iuliana (Journal of Research in Educational Sciences; Vol 15 No 1 (2024): JRES, Volume XV, Issue 1(17), Summer 2024DO - 10.14505/jres.v15.1(17).05, 2024)
Intellectual education prolonged and continuous self-instruction are the premises for transforming human resources into high-performing, competitive labor with major creative values and capabilities. The main factors highlighting the longevity and vitality of human resources are defined as education, intellectual work, and continuous training of intellectual functions. Today's society demands more than ever human resources capable of coping with the psycho-socio-cultural changes specific to the need to harmonize community realities with the realities of its own system. In this context, the necessity of introducing into the equation of training, the instruction of all categories of labor resources, the requirements of educational management through ensuring managerial competencies at the level of personnel in the education system, becomes apparent.